Towards the environmental geography concept - Kostrikov, Sergiy; Segida, Kateryna (Human Geography Journal, 2016)
Authors introduce the environmental geography concept. Environmental geography describes the spatial aspects of interactions between the human society and the natural environment. Spatial laws, trends and fluctuations make the environmental geography subject up. The paper examines briefly some regularities of this new discipline formation. As the key one among other methodological approaches the geomorphic method is selected for the watershed environment reconstruction. A relevant modeling example is introduced. A strong spatial aspect of this research implies GIS tools involvement, what is discussed in details, in particular – within human / environment interaction perspective.